Unintended Socio-economic Consequences of Reduced Supply of Active Open Spaces in the Perth Outer Metropolitan Growth Areas: A review of informing literature. - Tye, Marian; Middle, Garry; Costello, Diane; Hedgcock, David (WA Department of Sport and Recreation, 2012)
The implication for communities that don’t have access to active playing fields is that they will be more likely to miss out on the specific social and economic benefits attributable to such spaces and, in particular, the activities they support. Combining the three key factors of supply of active open space, demand for active open space and socio-economic vulnerability, the local governments in the outer metropolitan areas of Perth are significantly worse off than the middle and inner suburbs.